Institutional Interpretation of Human Rights: Critical Remarks - Nunzio Alì (Ethic@: an International Journal for Moral Philosophy)
Some scholars believe that only governments or those who uphold governmental policies can be human rights violators. Others argue that private individuals (with no governmental mandate and acting for themselves) are also able to violate human rights. The two positions have come to be known in the literature as the institutional interpretation and the interactional interpretation of human rights respectively. This paper critically analyzes an exemplary case: Thomas Pogge’s institutional conception of human rights as presented in World Poverty and Human Rights: Second Edition. This paper focuses on some of the negative consequences implicit in his approach. First of all, it shows that Pogge does not provide an adequate explanation of the reason why human rights should be conceived as claims on coercive social institutions and on those who uphold such institutions but not on single individuals, independently of their commitment to institutions. Secondly, it shows that official disrespect rather than violation as a criterion to evaluate the respecting of human rights is unsuccessful or at least insufficient. It sees in Pogge the same perspective mistake that infects Rawls’ conception of human rights, namely that of expanding unduly one of the functions human rights perform - establishing the limits of legitimate sovereignty - into their very essence. Therefore, this paper puts in question the way in which Pogge’s institutionalism mix the conception of human rights with the conception of (global) distributive justice. The conclusion to which the whole paper comes to is that proponents of the institutional interpretation (at least in the case of Pogge) misconstrue human rights because they conflate two philosophical agendas, that of human rights and that of global justice.